EFFECTS OF PRINCIPALS’ ADMINISTRATIVE PRACTICES ON TEACHERS’ JOB PERFORMANCE IN PUBLIC SECONDARY SCHOOLS IN KATHIANI SUB-COUNTY, KENYA - MUTUA, MARY MBITHE (Machakos University Press, 2022)
School principals’ administrative practices are an important management function in relation to obtaining, developing and motivating the human resources required by a school to achieve its objectives. The effectiveness of a principal’s administrative practices is reflected by the teacher job performance. This study sought to examine the principals’ administrative practices and their effects on teachers’ job performance in public secondary schools in Kathiani Sub-County, Machakos County. The objectives of the study were; to examine the effect of principals’ supervision practices on teachers job performance in public secondary schools in Kathiani Sub-County, to determine the effect of principals’ motivational practices on teachers’ job performance in public secondary schools in Kathiani Sub-County, to establish the effect of principals’ professional development practices on teachers job performance in public secondary schools in Kathiani Sub-County and to assess the effect of principals’ delegation of duty practices on teachers’ job performance in public secondary schools in Kathiani Sub-County. The study was based on path goal theory by Robert- House. The target population consisted of 32 principals and 107 teachers who were drawn from the 32 public secondary schools in the Sub-County. The researcher used stratified random sampling to sample the teachers and a census to select all the principals. Questionnaires and interviews were used as data collection instruments in this study. A pilot study was carried out, where a sample of 10% of the targeted population was used. This helped to ascertain the validity and reliability of the data collection instruments. The data collected was both quantitative and qualitative in nature. Quantitative data was analyzed through descriptive statistics. The descriptive statistics included frequencies and percentages. The Statistical Package for Social Sciences (SPSS) version 27 was utilized in running the analysis. The quantitative data was presented in form of pie charts, bar graphs and tables. On the other hand, qualitative data was analyzed using content analysis and was presented in continuous prose. The quantitative and the qualitative results revealed that principal supervision practices, principal motivation practices, principal professional development practices and principal delegation of duties affected teacher job performance. The study concluded that principals’ administrative practices affect teachers’ job performance in public secondary schools in Kathiani Sub-County, Kenya. The study recommends that the County Education Board, who is tasked with the responsibility of ensuring that schools offer quality education to students, should ensure that they allocate an adequate budget to facilitate in-service training for teachers.